2007
DOI: 10.1177/0959683607077010
|View full text |Cite
|
Sign up to set email alerts
|

Greenland (GISP2) ice core and historical indicators of complex North Atlantic climate changes during the fourteenth century

Abstract: The paper uses Greenland GISP2 ice core data together with historical documentary information to investigate the nature of climate changes that took place between AD 1270 and 1450 across the North Atlantic region. Detailed Deuterium and deuterium excess time series resolved to c. 8—10 samples per year are used to reconstruct relative changes in Greenland air temperature and past changes in sea surface temperature across the western North Atlantic. The data show that sea surface temperatures during the late thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 18 publications
2
44
0
1
Order By: Relevance
“…This was followed by a relatively warm interval and a second minimum at c. 1850 A.D. (Dahl-Jensen et al, 1998;Johnsen et al, 2001). Ice core accumulation data suggest little evidence for persistent changes during the period after 1200 A.D. (Andresen et al, 2004) although Deuterium and Na ++ records all point towards a significant change in moisture source after c. 1400 A.D. that may record a strengthening of meridional circulation (Dawson et al, 2007;Hoffmann et al, 2001;Kreutz et al, 1997;Mayewski et al, 1993).…”
Section: The Little Ice Age In Greenlandmentioning
confidence: 99%
“…This was followed by a relatively warm interval and a second minimum at c. 1850 A.D. (Dahl-Jensen et al, 1998;Johnsen et al, 2001). Ice core accumulation data suggest little evidence for persistent changes during the period after 1200 A.D. (Andresen et al, 2004) although Deuterium and Na ++ records all point towards a significant change in moisture source after c. 1400 A.D. that may record a strengthening of meridional circulation (Dawson et al, 2007;Hoffmann et al, 2001;Kreutz et al, 1997;Mayewski et al, 1993).…”
Section: The Little Ice Age In Greenlandmentioning
confidence: 99%
“…These climatic oscillations have been described in Greenland ice cores (e.g. O'Brien et al, 1995;Dawson et al, 2007), and in North Atlantic (e.g. Bond et al, 1997;Bianchi and McCave, 1999), Mediterranean (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Willard et al, 2005;Jalut et al, 2009) and tree rings (e.g. Esper et al, 2002;Moberg et al, 2005). Nevertheless, the overall lack of agreement about the worldwide distribution, precise timing, amplitude or cause of these fluctuations underlines the need for additional regional records to reconstruct climate change (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Blackford and Chambers (1995) were able to demonstrate this relationship using peat humidification records from Ireland, but noted no evidence of the Wolf Minimum or post-1900 relationship with solar variability. In the former case it is suggested that the North Atlantic climate, as evidenced by major reduction in the NAO prior to AD 1420, may have been operating very differently (Dawson et al 2007). Given the relationship between the NAO and AO it is likely the AO would also operate very differently in this time period.…”
Section: Causes Of Cold Spells In Irelandmentioning
confidence: 99%